Authentic Leadership (HBR Emotional Intelligence Series). - Review, Harvard Business (La Vergne : Harvard Business Review Press, 2017)
Organizations require certain qualities and behaviors from their employees, so much so that many individuals feel they lose who they truly are. Leaders, especially, can struggle to be seen as authority figures when they feel uncertain or emotional. Can you ever really be yourself at work? This book shows you how to balance vulnerability, emotion, and authority, so that you can feel effective at work while also being true to yourself. You'll learn from the latest research who is most at risk for feeling inauthentic, what that means for engagement and credibility, and how to decide when is appropriate to just be yourself--or adapt to your company's culture and expectations.--
Discovering your authentic leadership : why self-awareness is so critical / by Bill George, Peter Sims, Andrew N. McLean, and Diana Mayer -- The authenticity paradox : to grow, you need to feel like a fake / by Herminia Ibarra -- What bosses gain by being vulnerable : the psychology of human connection / by Emma Seppala -- Practice tough empathy : when you care, you show your true self / by Rob Goffee and Gareth Jones -- Cracking the code that stalls people of color : sacrificing identity to conform / by Sylvia Ann Hewlett -- For a corporate apology to work, the CEO should look sad : make your emotions match your message / by Sarah Green Carmichael -- Are leaders getting too emotional? : tears are OK if they're rare, an interview with Gautam Mukunda and Gianpiero Petriglieri / by Adi Ignatius and Sarah Green Carmichael.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Leadership -- Psychological aspects; Self-consciousness (Awareness); Authenticity (Philosophy); Corporate culture; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Authenticity (Philosophy); Corporate culture; Leadership -- Psychological aspects; Self-consciousness (Awareness); elektronické knihy; electronic books